Grazing was not mining: managing Victoria's goldfields commons. (22nd June 2018) - Davies, Peter; Lawrence, Susan; Twigg, Karen
Abstract: The great land rush of the eighteenth and nineteenth centuries saw vast swathes of temperate grazing land around the world pass into private hands. Commons and common lands, however, provided a vital interim mechanism in this shift from state control to private property ownership. Commons ensured continued and widespread access to natural resources, including water, minerals, soil, grass, and timber, that was integral to the colonial settler project. The gold rush in nineteenth‐century Victoria sheds important light on this process, where almost 250, 000 ha of Crown land were set aside as goldfields commons. These reserves maintained auriferous or gold‐bearing land in public hands and provided access to extensive tracts of grazing for the sheep and cattle of gold miners. In this paper, we examine how the traditional English notion of common lands was transferred to a New World environment and draw on the work of economist Elinor Ostrom to evaluate the use and function of Victoria's goldfields commons in terms of management, regulation, and sustainability.